A Late COVID-19 Complication: Male Sexual Dysfunction - Shoar, Saeed (Prehosp Disaster Med, 2020)
Since the beginning of the coronavirus infectious disease 2019 (COVID-19) pandemic, an exponentially large amount of data has been published to describe the pathology, clinical presentations, and outcomes in patients infected with the severe acute respiratory syndrome novel coronavirus 2 (SARS-CoV-2). Although COVID-19 has been shown to cause a systemic inflammation predisposing the involvement of multiple organs, its mechanism affecting the urogenital system has not been well-documented. This case report presents the clinical course of two male patients with COVID-19 who developed sexual dysfunction, as anorgasmia, following recovery from the infection. Although no evidence of viral replication or inflammatory involvement could be identified in these cases’ urogenital organs, a lack of other known risk factors for anorgasmia points to the role of COVID-19 as the contributing factor.